Surface Analysis and Digitization of Components Manufactured by SLM and ADAM Additive Technologies - Timko, Pavol; Holubjak, Jozef; Bechny, Vladimir; Novak, Martin; Czan, Andrej; Czanova, Tatiana (Manufacturing Technology Journal, 2023)
The presented article focuses on the surface analysis of the components manufactured by different additive technologies and their reverse digitization. Sintered components were manufactured by SLM and ADAM technologies, while their surface was analyzed using a progressive optical measurement method. To examine the possibility of reverse engineering, the components were optically scanned with a laser scanner and compared to their CAD model. Based on empirical experience, to scan opti-cally the metal and lustrous surfaces is a challenge. The components were manufactured from anti-corrosion materials 17-4 PH and 316L-0407.
Keywords: Additive manufacturing; Sintering; Optical scanning; 17-4 PH; 316L-0407; SLM; Surface texture